Seizures, periodic and rhythmic patterns in primary intraventricular hemorrhage - Christoph Stretz; Zubeda Sheikh; Carolina B. Maciel; Lawrence J. Hirsch; Emily J. Gilmore (Annals of Clinical and Translational Neurology, 2018)
Abstract Objective Primary intraventricular hemorrhage (pIVH) uncommonly presents with seizures. There are no prior data regarding the frequency of seizures, periodic and rhythmic patterns on continuous electroencephalography (EEG), (cEEG) in these patients. Methods We retrospectively assessed frequency of seizures, periodic discharges, and rhythmic patterns in pIVH patients undergoing cEEG monitoring. We reviewed indications for cEEG, demographics, GCS at presentation and during cEEG, modified Graeb score (mGS), presence of hydrocephalus, cEEG duration, findings and use of antiseizure medications (ASM). cEEG patterns were classified according to location and morphology. All patterns were considered “hyperexcitable” except GRDA. The ictal‐interictal continuum (IIC) was defined as LRDA, PDs, and/or SW >1 Hz but <2.5 Hz, not meeting criteria for definite electrographic seizures. Results Eleven patients had pIVH with median age of 81 (46–87) years and median mGS of 15 (9–23). Hydrocephalus was present in 7 (63.6%) and all underwent external ventricular drain (EVD) placement. Median cEEG recording was 19 (12–156) hours. Periodic or rhythmic EEG patterns were seen in 7 of 11 (64%), 5 of which were “hyperexcitable”. For the 5 patients with pIVH, EVDs, and hyperexcitable patterns, 4 (80%) were lateralized contralateral to the EVD and 1 (20%) was generalized to the EVD. The only significant difference between the hyperexcitable and non‐hyperexcitable group was duration of cEEG monitoring (P = 0.007). Interpretation Hyperexcitable patterns were common in our cases. Further research is warranted to assess prevalence of hyperexcitable patterns, their risk factors, underlying pathophysiology, and association with neuronal injury in pIVH.